2018
DOI: 10.1186/s10020-018-0049-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric expression of H19 and ADIPOQ in concave/convex paravertebral muscles is associated with severe adolescent idiopathic scoliosis

Abstract: BackgroundAdolescent idiopathic scoliosis (AIS) is the most common paediatric spinal deformity. The etiology and pathology of AIS remain unexplained, and have been reported to involve a combination of genetic and epigenetic factors. Since paravertebral muscle imbalance plays an important role in the onset and progression of scoliosis, we aimed to investigate transcriptomic differences by RNA-seq and identify significantly differentially expressed transcripts in two sides of paravertebral muscle in AIS.MethodsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 62 publications
(77 reference statements)
2
49
1
Order By: Relevance
“…PSM plays a significant role in spine stability and postural control, and some investigators have suggested that the muscle plays a significant role in the initiation and progression of AIS [ 2 , 8 ]. In recent decades, bilateral PSM asymmetry in AIS has been widely discussed in terms of histology [ 8 , 12 , 13 ], muscle morphology [ 2 , 11 ], molecular biology [ 7 ], and biomechanical characteristics [ 5 ]. In particular, many studies have focused on the pathological changes of muscle fiber type-specific characteristics, revealing a numerical predominance of muscle fiber type I on the convex side [ 8 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSM plays a significant role in spine stability and postural control, and some investigators have suggested that the muscle plays a significant role in the initiation and progression of AIS [ 2 , 8 ]. In recent decades, bilateral PSM asymmetry in AIS has been widely discussed in terms of histology [ 8 , 12 , 13 ], muscle morphology [ 2 , 11 ], molecular biology [ 7 ], and biomechanical characteristics [ 5 ]. In particular, many studies have focused on the pathological changes of muscle fiber type-specific characteristics, revealing a numerical predominance of muscle fiber type I on the convex side [ 8 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin role is the attenuation of the excessive inflammatory response in the wall of the blood vessels of the placenta through inhibition of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling (it is a protein complex that controls transcription of deoxyribonucleic acid (DNA) and cytokine production), decreasing CRP (C-reactive protein) and increasing nitric oxide [42] via activating endothelial nitric oxide synthase and inhibition of superoxide in endothelial cells [43]. Besides, adiponectin mediated the process of trophoblast invasion by modulation of MMP/TIMP (matrix metalloproteinase to tissue inhibitor of metalloproteinase) balance (this is a ratio between active extracellular [11][12][13], hyperlipidemia [22], diabetic kidney disease [30], polycystic ovary [32], ovarian cancer, gestational diabetes [39], systemic sclerosis [74], breast cancer [98], lung cancer [99], colon cancer [100], thyroid cancer [106], prostate cancer [108,109], glioblastoma [113], AIS [129], Duchene Muscular Dystrophy [132], pulmonary hypertension [149], obstructive sleep apnea [151], atherosclerosis [11], hypertension [158], preeclampsia [41][42][43][44], COVID-19 [164] Cervical & endometrial cancer [37,38], joint inflammation [64], bone erosion in rheumatoid arthritis [65], SLE with renal involvement [87] Adipsin Systemic sclerosis with PAH [83], SLE with renal involvement [ Insulin resistance &diabetes [11,…”
Section: • Preeclampsiamentioning
confidence: 99%
“…Moreover, adiponectin appears to play a role in regulating muscle mass and acts as a critical signal for muscle regeneration and suppression of proteolysis [128]. In a study of adolescent idiopathic scoliosis (AIS), a common form of spinal deformity, it was mentioned that adiponectin deficiency was involved in unequal bilateral development of the paravertebral muscles that ended in the development of lateral curvatures of the spine [129].…”
Section: Adipocytokines and Musclesmentioning
confidence: 99%
“…(2) studies that involved the analysis of human posture deviations but considering only isolated body segment analysis such as arms and legs without spinal assessment (i.e., without evaluating spine misalignment); (3) papers that identified variations in body position regarding the balance; (4) papers with text unavailable in full; (5) papers that used mobile applications exclusively based on wearable devices.…”
Section: Selection Criteriamentioning
confidence: 99%
“…However, due to numerous structural overloads or congenital disorders which people are subjected to, as well as age-related modifications (e.g., muscle strength reduction and reduced range of motion), many individuals develop changes in the body alignment that can culminate in severe postural deviations. These alterations have a multifactorial etiology and can also be genetic, such as adolescent idiopathic scoliosis (AIS) [5] and Hyperkyphosis [6].…”
Section: Introductionmentioning
confidence: 99%